(untitled) (Journal of Engineering, 2021)
Experimental model was done for pile model of L / D = 25 installed into a laminar shear box contains different saturation soil densities (loose and dense sand) to evaluate the variation of pore water pressure before and after apply seismic loading. Two pore water pressure transducers placed at position near the middle and bottom of pile model to evaluate the pore water pressure during pullout tests. Seismic loading applied by uniaxial shaking table device, while the pullout tests were conducted through pullout device. The results of changing pore water pressure showed that the variation of pore water pressure near the bottom of pile is more than variation near the middle of pile in all tests. The variation of pore water pressure after apply seismic loading is more than the variation before apply seismic loading near the middle of pile and near the bottom of pile and in loose and dense sand. Variation of pore water pressure after apply seismic loading and uplift force is less than the variation after apply seismic loading in loose sand at middle and bottom of pile.